The Social Responsibility of the Area Excise Office, Chachoengsao Province - Sintrap, Chayanan; Prayongtrap, Yupha; Udomtawi, Kacanibha (Academic MCU Buriram Journal, 2016)
The objectives of this qualitative research were: 1) to study problems the social responsibility of the area excise office, chachoengsao province; 2) to study enterprise master social responsibility; and 3) to study model are suitable the social responsibility of the area excise office,chachoengsao province, Contributors to the issue of social responsibility of seven people the data underlying the corporate social responsibility of the three people who provide information on the proper form of corporate social responsibility. By Group The target group of 10 instruments in the interview form and explain the findings of the second edition of the lecture series. The study found that: According to problems about a problems the social responsibility of the area excise office, Chachoengsao province, show that Economic problems have planned litigation related to the production and sale of alcohol. Environmental A performance improvement in the social responsibility of planning a human rights legal issues regarding the implementation of measures in favor of the excise tax revenue to the state to take seriously. Owing to the enterprise master social responsibility, show that The event to hear the community’s major social responsibility standards ISO 2600 organizers Kathin PEA. Event Medical The recycling center The school project to reduce energy consumption. 3. According to guidelines for model are suitable the social responsibility of the area excise office, Chachoengsao province, show that a project to develop social responsibility projects Excise fourth passer. Proactive public relations program to promote income generation for communities legally. The conversion of the community for the benefit of farmers in the fermented tobacco and alcohol destroyed by the arrest of excise, to prevent and eliminate pests. And projects to share my blood.